2018
DOI: 10.21449/ijate.430720
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Performance of Missing Data Imputation Methods in IRT Analyses

Abstract: Abstract:Missing data is a common problem in datasets that are obtained by administration of educational and psychological tests. It is widely known that existence of missing observations in data can lead to serious problems such as biased parameter estimates and inflation of standard errors. Most of the missing data imputation methods are focused on datasets containing continuous variables. However, it is very common to work with datasets that are made of dichotomous responses of individuals to a set of test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…Since differences between missing data rate are not important, Random Forest and MICE can support up to 50% of missing rate at an optimal sample size of 200. Results are not in agreement with those of [43] who found that error decreased when the sample size increase no matter the missing rate. The difference might be explained by the fact that in our study imputed data pass through the network before evaluating the performances.…”
Section: Effect Of Imputation Methods On Size and Missing Data Ratecontrasting
confidence: 99%
“…Since differences between missing data rate are not important, Random Forest and MICE can support up to 50% of missing rate at an optimal sample size of 200. Results are not in agreement with those of [43] who found that error decreased when the sample size increase no matter the missing rate. The difference might be explained by the fact that in our study imputed data pass through the network before evaluating the performances.…”
Section: Effect Of Imputation Methods On Size and Missing Data Ratecontrasting
confidence: 99%
“…The use of EM as an imputation method has been studied in the literature of psychometrics (e.g., [47,52,53]). Results suggested that the EM imputation might work well for polytomous data (e.g., [53]), whereas it yielded a greater bias in IRT parameter estimations than other methods (e.g., MI, [47,52]) when the data were dichotomous. Part of the reason, according to Finch [47], might lie in that the multivariate normality assumption usually does not hold for dichotomous data.…”
Section: Em Imputationmentioning
confidence: 99%
“…Database schema differences among the contributing sources will cause data sets originated from the source with lack of attributes to be missing values within the merged data sets [2]. • Respondents' answering behavior: In survey data, missing values are often caused by reasons like respondents refuse to answer the survey or they do not understand the questions in the questionnaires [25], [26]. • Error in data collection tools: Research data is also prone to missing values problem due to an error in data collection tool (such as sensors) or human researcher's fault.…”
Section: A Reasons Of Missing Datamentioning
confidence: 99%
“…This approach leads to the lack of sufficient data to complete an analysis and thus may give misleading results [27], [28]. Kalkan (2018) stated that although there is a direct correlation between the rate of missing values and the quality of statistical analysis, there is no acceptable proportion of missing values in the data set for the correct statistical conclusion [29], [26]. However, Schafer (1999) argued that the ratio of 5% or less of missing values is inconsequential [30].…”
Section: A Reasons Of Missing Datamentioning
confidence: 99%